Notary Role in Implementing the Credit Agreement and Process of Binding Liability - Dian Oktavian Anggraeni; Sukarmi Sukarmi (Sultan Agung Notary Law Review, 2020)
The objectives of this research are: 1) To determine the role of the Notary in implementing the credit agreement and binding Mortgage Rights, 2) To find out the obstacles faced by the Notary in implementing the credit agreement and binding the Mortgage, 3) To find out the solutions provided by the Notary in implementing the credit agreement and binding Mortgage Rights. The data used in this study are primary and secondary data collection, which can support the assessment, which is then analyzed using a sociological approach. Based on the research results concluded that: 1) The role of the Notary in the implementation and process of binding Mortgage Rights lies in his responsibility. Namely the responsibility for the credit agreement deed made by him and the legal protection of the parties involved in the deed if there is a dispute between the parties in the future, then that becomes a reference for the authorized legal official., 2) Constraints faced by the Notary such as the inability of the parties, the difficulty of the parties in completing the terms of the credit agreement and bonding of Mortgage Rights, the registration process of Mortgage Rights at BPN which is too long, 3) The solution provided by the Notary is to reschedule the implementation of the credit agreement or authorize another party if unable to attend, complete the requirements credit agreement and bonding of Mortgage Rights by asking for help from a Notary partner, charging fees to the Customer to speed up the registration process at BPN